2018
DOI: 10.1186/s42358-018-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of scrotal involvement in children and adolescents with IgA vasculitis

Abstract: Objective: To characterize scrotal involvement in children and adolescents with IgA vasculitis. Methods: A cross-sectional retrospective study included 296 IgA vasculitis (EULAR/PRINTO/PRES criteria) patients, 150/296 (51%) were males and assessed by demographic/clinical/laboratory and treatments. Scrotal involvement was defined by the presence of scrotal edema and/or pain/tenderness in physical examination and/or testicular Doppler ultrasound abnormalities. Results: Scrotal involvement was observed in 28/150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…A lower frequency of elevated serum IgA in GI involvement has not been previously reported. Data in the literature is scarce; nevertheless, a recent study in children found significantly lower serum IgA in IgAV patients with scrotal involvement versus those without this manifestation [19]. And a study on biomarkers of childhood IgAV nephritis showed no significant differences in the serum IgA level comparing cases with and without nephritis [20].…”
Section: Discussionmentioning
confidence: 99%
“…A lower frequency of elevated serum IgA in GI involvement has not been previously reported. Data in the literature is scarce; nevertheless, a recent study in children found significantly lower serum IgA in IgAV patients with scrotal involvement versus those without this manifestation [19]. And a study on biomarkers of childhood IgAV nephritis showed no significant differences in the serum IgA level comparing cases with and without nephritis [20].…”
Section: Discussionmentioning
confidence: 99%
“… 1 3 Orchitis was described as the presence of scrotal swelling and/or tenderness in physical exam and/or testicular Doppler ultrasound alterations. 2 The duration of orchitis was measured in days.…”
Section: Methodsmentioning
confidence: 99%
“…Nephritis was defined as hematuria >5 red blood cells/high power field or presence of red blood cells in the urinary sediment and/or proteinuria >0.1g/m 2 /day. Nephrotic syndrome was diagnosed according to edema, serum albumin <2.5g/L and proteinuria >1g/m 2 /day.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations